1995
DOI: 10.1300/j010v21n04_05
|View full text |Cite
|
Sign up to set email alerts
|

Supportive and Unsupportive Interactions as Perceived by Cancer Patients

Abstract: This exploratory qualitative study was undertaken to expand our knowledge of cancer patients' perceptions of supportive and unsupportive interactions with members of their social networks and the factors that lead them to evaluate certain kinds of support as helpful and others as unhelpful. Fifteen cancer patients were interviewed using a structured interview schedule. The interview focused on several aspects of the social support process, including types of helpful and unhelpful behaviours, perceived continge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 0 publications
2
22
0
Order By: Relevance
“…Findings from this investigation with melanoma patients are in accord with those reported by previous researchers (Bloom, 1982;De Boer et al, 1999;Gurowka & Lightman, 1995;Mishel & Braden, 1988;Thoits, 1986;Wortman, 300 RUDY, ROSENFELD, GALASSI, PARKER, SCHANBERG 1984). Among these findings, are that (a) former patients can provide new patients with useful information about their illness, its symptoms, and treatment; (b) effective support can come from socially similar others who have faced and successively coped with stress from the illness; (c) knowing that one's feelings about being diagnosed with melanoma are not unique helps to reduce patients' sense of isolation and despair; and (d) becoming aware of former patients' experiences with the disease helps to increase feelings of strength and security.…”
Section: Helpees and Helpers Perceive That A Peer-helper Telephone-bsupporting
confidence: 91%
See 3 more Smart Citations
“…Findings from this investigation with melanoma patients are in accord with those reported by previous researchers (Bloom, 1982;De Boer et al, 1999;Gurowka & Lightman, 1995;Mishel & Braden, 1988;Thoits, 1986;Wortman, 300 RUDY, ROSENFELD, GALASSI, PARKER, SCHANBERG 1984). Among these findings, are that (a) former patients can provide new patients with useful information about their illness, its symptoms, and treatment; (b) effective support can come from socially similar others who have faced and successively coped with stress from the illness; (c) knowing that one's feelings about being diagnosed with melanoma are not unique helps to reduce patients' sense of isolation and despair; and (d) becoming aware of former patients' experiences with the disease helps to increase feelings of strength and security.…”
Section: Helpees and Helpers Perceive That A Peer-helper Telephone-bsupporting
confidence: 91%
“…Van den Borne, Pruyn, and Van Dam de Mey (1986), in their review of 18 articles concerned with the effects of contacts between cancer patients, found several positive effects, such as a reduction in phobias and negative feelings. Thus, a special understanding seems to flow from interacting with individuals who have had similar experiences (Gurowka & Lightman, 1995). Thus, a special understanding seems to flow from interacting with individuals who have had similar experiences (Gurowka & Lightman, 1995).…”
Section: Social Support From Similar Othersmentioning
confidence: 99%
See 2 more Smart Citations
“…Limited research has addressed why caregivers interpret others' actions as helpful or unhelpful (Gurowka & Lightman 1995). However, studies of other populations have identified expectations as influences on the appraisal of interactions as supportive or nonsupportive (Gottlieb 1992, Sarason et al . 1994, Canary et al .…”
Section: Unmet Expectationsmentioning
confidence: 99%